FY2015-FY2017 Medium-Term Budget. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
The proposed FY 15-17 Medium-Term Budget (MTB) was formulated within the Fund's strategic planning framework to align allocation of resources to the delivery of institutional priorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Budget; Capital Budget; Dollar; PP; United States